A Framework for Increasing the Flow Efficiency in a Public Organisation through Operations Management Principles - A Case Study at the Swedish Migration Board - Iversen, Carina; Louise, Sandén (My University, 2014)
The public sector has a tradition of bureaucracy, political influence and conflicting stakeholder interests, which historically has resulted in that the public sector has fallen behind the industry regarding operational improvement work. The demand for more efficient processes in the public sector has increased and attempts have therefore been made to adapt successful concepts from the industry such as Operations Management principles. There are several examples where Operations Management principles within the private sector have been successful. However, the theory of applying Operations Management in the public sector is insufficient and requires further research. Therefore, the purpose of this study is to contribute with knowledge on how to increase flow efficiency in a public organisation by adopting Operations Management principles. This was done through an analysis of the asylum process at the Swedish Migration Board, hereafter referred to as the board, where the process was examined and evaluated and proposals for increased flow efficiency was developed. The board is a governmental organisation whose main field of responsibility is to consider applications from people who want to visit, live in, or seek asylum in Sweden and the focus of this study is the asylum process. With current conflicts around the world there is an increased demand for protection and the inflow of asylum seekers to Sweden have increased with approximately 50 % between 2013 and 2014. The board is therefore facing a challenge to meet the increased demand with acceptable waiting times, wherefore it has been requested to evaluate if the way of working is sufficient for the organisation. Based on the current theory, a conceptual framework was created in order to adapt Operations Management principles in public organisations. Based on the framework, an analysis of the current flow efficiency in the asylum process was conducted, and it was identified that the board has issues with high inventory levels in the system and thereby long waiting times in the asylum process. Moreover, there is a significant variation in the asylum process due to both internal and external factors that increases the total throughput time. The organisational design of the board is functional with a top-down decision making and control. The employees are organised in “silos” with deficiencies in both horizontal and vertical communication, which leads to limited insight in the work of others. Moreover, there is a lacking capacity of human resources that further increases the throughput times. The daily work is controlled by insufficient productivity goals that lead to sub-optimised processes and less ability for the employees to stop the process if defects are detected. In order to increase the flow efficiency a number of improvement proposals have been identified. First of all, it is urgent to reduce the inventory levels in the system in order to reduce false demands and increase the value adding time in the process. In order to do so, the performance goals must be changed, and the method should be controlled rather than the productivity. Furthermore, the variations in the system must be reduced, wherefore different flows with similar characteristics should be separated. Finally, the communication within the organisation as well as between the organisation and external operators must be enhanced. With these proposals, the flow efficiency can be increased in the public organisation through Operations Management principles.
Keywords: Övrig industriell teknik och ekonomi; Produktion; Transport; Other industrial engineering and economics; Production; Transport